HAUGHT, GOLSHANI AND THE SCIENTIFIC VIEWPOINT OF STATE ISLAMIC UNIVERSITY IN INDONESIA - Muhammad Thoyib (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2014)
This article aims to examine the scientific view of the State Islamic University in Indonesia, namely, the concept of 'integration of science and religion'. The theory used is based on 'theology theory of evolution' of John F. Haught and theory of Islamic Science of Mehdi Golshani. State Islamic University such as UIN Sunan Gunung Djati Jakarta, UIN Syarif Hidayatullah Jakarta and other UIN, authorized open course, both of science humanities, social, technical and religious faculty. Referring to the Haught and Golshani‟s views, there are three approaches in the development of Islamic science in UIN; First, science aims to find the meaning of Allah (ontological); second, dismantle and re-test the findings of the medieval Islamic scientists (epistemological); Third, utilizing science to build a better civilization (axiological). Thus, UIN‟s existence in the future is largely determined by the success or failure of these institutions to develop the three areas of science Islam.